REVOCATION OF REGIONAL REGULATIONS AND ECONOMIC PERFORMANCE IN INDONESIA: PROVINCIAL PANEL DATA 2002-2009 - Nugroho, Adityo; Ariutama, I Gede Agus (JURNAL INFO ARTHA, 2016)
The aim of this study is to investigate the impact of regional regulation on economic performance in Indonesia. This study uses a panel data set of 31 Provinces in Indonesia during the period of 2002 to 2009 and applies fixed effect method for its estimation. In order to provide better explanation, this study also utilize three proxies of regional regulation variables, namely the number of regional regulations, the number of revoked regional regulations, and ratio of the revoked regional regulations to the existing regional regulations.The result of this study shows that regional regulation negatively affects economic performance. However, the coefficient of regional regulation is insignificant. In general, it can be concluded that there is not enough evidence to claim that regional regulation affect economic performance. Still, by classifying regions into two groups, rich and poor regions, the significant effect of regional regulation on economic development varies.